2011
DOI: 10.1159/000324775
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Submucosal Administration of Antigen-Presenting Cells Induces Effective Immunological Responses in Cancer Immunotherapy

Abstract: Human NKT cells are known to have strong antitumor activities and to be activated by specific ligand, α-galactosylceramide (αGelCer). We examined the migration pattern of αGalCer-pulsed DCs and the immune responses after administration by different routes. DCs injected into nasal submucosa quickly migrated to the lateral neck lymph rather than the lateral lymph nodes. The absolute number of NKT cells and the IFN-γ-producing cells increased in peripheral blood after injection of the DCs into nasal submucosa. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…We have reported previously that DCs isolated from PBMCs of patients with head and neck cancer migrated to CLNs after oral submucosal administration , and we showed that this treatment was safe . Simultaneous administration of an antigen with α‐GalCer‐DCs is thus an accessible way to activate iNKT cells in regional lymph nodes; however, further studies are needed to clarify the role of activated iNKT cells in regional lymph nodes in treatment of AR.…”
Section: Discussionmentioning
confidence: 80%
“…We have reported previously that DCs isolated from PBMCs of patients with head and neck cancer migrated to CLNs after oral submucosal administration , and we showed that this treatment was safe . Simultaneous administration of an antigen with α‐GalCer‐DCs is thus an accessible way to activate iNKT cells in regional lymph nodes; however, further studies are needed to clarify the role of activated iNKT cells in regional lymph nodes in treatment of AR.…”
Section: Discussionmentioning
confidence: 80%
“…This activation is associated with increased serum levels of cytokines that stimulate the growth and function of T cells [IL-12 ( 150 , 175 ) and IL-2 receptors ( 175 )] and other factors that enhance natural killer cell activity (i.e., interferon gamma [IFN-γ] ( 150 , 155 , 156 , 158 , 161 , 163 , 172 ), CD16 ( 175 ), and tumor necrosis factor α [TNF-α]) and immune cell maturation (GMCSF) ( 164 ). In eleven out of twelve completed phase I-II clinical trials, tumor regression, stable disease, partial response or increased median survival time were observed in a subgroup of patients ( 153 , 157 , 159 , 160 , 162 169 ). These promising clinical findings are associated with the activation of natural killer cells, cytotoxic CD8+ T cells and CD4+ T cells, which are the most relevant immune responses to cancer ( 230 ).…”
Section: α-Galactosylceramide (α-Galcer)mentioning
confidence: 99%
“…The other fi ve patients had stable disease. In a recent trial, 17 HNSCC patients were enrolled in a study comparing APC administration via the nasal mucosa with administration via the oral mucosa [96]. An increase in activated NKT cells was detected in patients receiving α-GalCer-loaded APCs administrated via the nasal mucosa.…”
Section: Adoptive Cell Transfermentioning
confidence: 99%